Young globular clusters in NGC1316 - Sesto, Leandro Alberto (2018)
We present multi-object spectroscopy of the inner zone of the globular cluster (GC) system associated with the intermediate-age merger remnant NGC1316. Using the multi-object mode of the GMOS camera, we obtained spectra for 35 GCs. We find pieces of evidence that the innermost GCs of NGC1316 rotate almost perpendicular to the stellar component of the galaxy. In a second stage, we determined ages, metallicities, and α-element abundances for each GC present in the sample, through the measurement of different Lick/IDS indices and their comparison with simple stellar populationmodels.We confirmed the existence of multiple GC populations associated with NGC1316, where the presence of a dominant subpopulation of very young GCs, with an average age of 2.1 Gyr, metallicities between -0.5 < [Z/H] < 0.5 dex, and α-element abundances in the range -0.2 < [α/Fe] < 0.3 dex, stands out. Several objects in our sample present subsolar values of [α/Fe] and a large spread of [Z/H] and ages. Some of these objects could actually be stripped nuclei, possibly accreted duringminor merger events. Finally, the results have been analysed with the aim of describing the different episodes of star formation and thus provide a more complete picture about the evolutionary history of the galaxy. We conclude that these pieces of evidence could indicate that this galaxy has cannibalized one or more gas-rich galaxies, where the last fusion event occurred about 2 Gyr ago.